Scrapbooks, Snapshots and Memorabilia Hidden Archives of Performance - McGillivray, Glen (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2011)
Scrapbooks, Snapshots and Memorabilia: Hidden Archives of Performance asks the questions: What constitutes an archive? What is worthy of being archived? And who decides? Performances are ephemeral, so archival questions of selection and appraisal determine which performances will be remembered by history and which will not. The essays in this collection each explore a different facet of the ephemerality of performance, and the traces it leaves behind: from photographic stills of actors or sets; draft scripts and production notes, theatre programs and reviews; the language used to evoke the experience of watching a dance; to the memories contained within a site which has been used for a site-specific performance. Each of the contributors to Scrapbooks, Snapshots and Memorabilia employs pertinent case studies to reveal performances that are so often 'hidden' from the authoritative archival view; for example, those by women, indigenous people, amateurs and working people, and those outside metropolitan centres. In this way, they build a powerful argument for reconsidering - or at the very least, broadening - notions of what the performance archive can be.